Using differential ratings of perceived exertion to assess agreement between coach and player perceptions of soccer training intensity: An exploratory investigation - Macpherson, T. W.; McLaren, S. J.; Gregson, W.; Lolli, L.; Drust, B.; Weston, M. (Journal of Sports Sciences, 2019)
We aimed to assess the coach-player agreement of subjective soccer training loads via differential ratings of perceived exertion (dRPE). The coach initially underwent quantifiable familiarisation (blackness test) with the Borg CR100 scale. Data were collected from 16 semi-professional soccer players across seven consecutive training sessions. For the measurement of subjective training load, the coach and players provided dRPE (CR100) for legs (RPE-L), breathlessness (RPE-B) and technical exertion (RPE-T). Coach-prescribed dRPE were recorded prior to training, with coach observed and player reported dRPE collected post training. Statistical equivalence bounds for agreement between coach (prescribed and observed) and player reported dRPE scores were 4 arbitrary units on the CR100 and we used a probability outcome of likely (=75%) to infer realistic equivalence. Following three familiarisation sessions, the coach improved their blackness test score from 39% to 83%. Coach observed and player reported RPE-T scores were likely equivalent, with all other comparisons not realistically equivalent. Since training prescription is coach-led, our data highlight the importance of accurate internal load measurement and feedback in soccer. The improved accuracy and precision of coach intensity estimation after three attempts at the blackness test suggests that this method could be worthwhile to researchers and practitioners employing dRPE.